The association between lifestyle and hypertension among elderly: A cross-sectional study at the Merdeka Community Health Center, Karo Regency - Br Surbakti, Chindy; Hartono, Hartono; Siregar, Santy Deasy; Munadi, Munadi; Yensuari, Yensuari; Marpaung, Hans Hotma Haposan; Riskaldy, Riskaldy; Meilani, Inda Kania (Buletin Kedokteran & Kesehatan Prima, 2025)
Background: Hypertension is a non-communicable disease with a continually rising prevalence, particularly within the elderly population. Lifestyle factors play a critical role in influencing the risk of developing hypertension. This study aimed to determine the relationship between lifestyle and the incidence of hypertension among the elderly at Merdeka Health Center in 2025. Methods: This study employed a quantitative design with a descriptive correlational method and a cross-sectional approach. The study population consisted of all 125 elderly individuals who visited the Merdeka Health Center between January and December 2024. A sample of 55 respondents was selected using an accidental sampling technique. Data were collected through questionnaires and blood pressure measurements and were subsequently analyzed using the Spearman's rho correlation test with a significance level of α=0.05. Results: The findings indicated a significant relationship between physical activity (p=0.046;r=−0.270), dietary patterns (p=0.029;r=0.295), rest/sleep habits (p=0.007;r=0.361), pesticide exposure (p=0.009;r=−0.351), and family history of hypertension (p=0.000;r=0.512) with the incidence of hypertension in the elderly. However, no significant relationship was found between smoking history and the incidence of hypertension (p=0.057;r=−0.258). Conclusion: Most of the investigated lifestyle components—specifically physical activity, dietary patterns, and rest habits—along with pesticide exposure and family history, have a significant association with the incidence of hypertension in the elderly. It is therefore recommended that elderly individuals adopt a healthy lifestyle for the prevention and control of hypertension.